2015
DOI: 10.20360/g2cp49
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Digital Devices and Preschoolers’ Home Multiliteracy Practices

Abstract: The increased use of digital devices such as touchscreen tablets in the home for work, communication, entertainment, and information searching makes them naturally attractive to toddlers and preschoolers who learn to communicate by observing and interacting with parents and older siblings. This paper presents one of the major findings from a study in Canada and Australia that examined preschoolers' (ages 3 to 5) home multiliteracy practices. By focusing on data from one of the participants in this study, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…For almost two decades, the AAP has called for no screen time for children under the age of two years. Libraries, preschools and childcare centres promote these recommendations in their programmes, and yet, qualitative researchers have documented beneficial uses of digital technology by children in their homes and with their families (Marsh et al., 2015, 2017; McPake et al., 2013; Plowman et al., 2008; Wong, 2015). My lived experiences described in this paper personify the tension between the two camps of scholarly research on infants and toddlers using digital technology.…”
Section: Negotiating Screen Time: a Mother’s Struggle Over ‘No Screenmentioning
confidence: 99%
“…For almost two decades, the AAP has called for no screen time for children under the age of two years. Libraries, preschools and childcare centres promote these recommendations in their programmes, and yet, qualitative researchers have documented beneficial uses of digital technology by children in their homes and with their families (Marsh et al., 2015, 2017; McPake et al., 2013; Plowman et al., 2008; Wong, 2015). My lived experiences described in this paper personify the tension between the two camps of scholarly research on infants and toddlers using digital technology.…”
Section: Negotiating Screen Time: a Mother’s Struggle Over ‘No Screenmentioning
confidence: 99%
“…Many researchers have explored the possibility that the touchscreen promotes learning (Romeo et al, 2003; Crescenzi et al, 2014; Wong, 2015). One study with adults found that the interactive feature (e.g., dragging an object across the screen) could improve mathematical learning performance (Dubé and McEwen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies describe how mobile digital technology (DT), such as smartphones and tablet computers, are being used to support young children's literacy learning at home and at school, and to create a school-to-home link (Neumann, 2016;Radesky, Schumacher, & Zuckerman, 2015;Wong, 2015;Blagojevic, Brumer, Chevalier, O'Clair, & Thomes, 2012). While some studies have examined the use of e-Books, e-games, digital drawing pens (Lee, Wu, & Chen, 2017), augmented reality toys (Yilmaz, 2016) and learn-to-read apps, studies that report on the use of open-ended iPad apps in school environments are emerging (e.g., Fleer, 2014;Herro, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%